ACAF 1 : First Australian Contemporary Art Fair. - ACAF 1 : First Australian Contemporary Art Fair, Melbourne, 1988 (Melbourne : ACGA (Australian Commercial Galleries Association), 1988)
Mitelman, Allan ; Madigan, Rosemary ; Brown, Leonard ; Rapotec, Stan ; Zusters, Reinis ; Herman, Sali ; Harris, Steve ; Harvey, Geoff ; Proud, Geoffrey ; Taylor, Neil ; Ben ; Parr, Mike ; Rankin, David ; Fries, Ernst ; etc.
ACAF 1 : First Australian Contemporary Art Fair, Royal Exhibition Building, Melbourne, 23 - 31 July 1988
boek